2016
DOI: 10.1186/s13567-016-0377-2
|View full text |Cite
|
Sign up to set email alerts
|

The activation of p38MAPK and JNK pathways in bovine herpesvirus 1 infected MDBK cells

Abstract: We have shown previously that BHV-1 infection activates Erk1/2 signaling. Here, we show that BHV-1 provoked an early-stage transient and late-stage sustained activation of JNK, p38MAPK and c-Jun signaling in MDBK cells. C-Jun phosphorylation was dependent on JNK. These early events were partially due to the viral entry process. Unexpectedly, reactive oxygen species were not involved in the later activation phase. Interestingly, only activated JNK facilitated the viral multiplication identified through both che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…However, the effects of EGFR on BoHV-1 infection are currently unknown. Given that the canonical EGFR downstream effects including PLC-γ1, MAPK, Akt and JNK are unanimously activated during BoHV-1 productive infection in MDBK cells [19,20], we hypothesized that BoHV-1 infection activates EGFR signaling to facilitate viral replication. Furthermore, it has been reported that EGFR is activated in response to radiation-induced DNA damage to promote cell survival [21], and in BoHV-1-infected A549 cells, detectable DNA damage is induced at 24 and 48 hours (h) after infection [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of EGFR on BoHV-1 infection are currently unknown. Given that the canonical EGFR downstream effects including PLC-γ1, MAPK, Akt and JNK are unanimously activated during BoHV-1 productive infection in MDBK cells [19,20], we hypothesized that BoHV-1 infection activates EGFR signaling to facilitate viral replication. Furthermore, it has been reported that EGFR is activated in response to radiation-induced DNA damage to promote cell survival [21], and in BoHV-1-infected A549 cells, detectable DNA damage is induced at 24 and 48 hours (h) after infection [22].…”
Section: Introductionmentioning
confidence: 99%
“…In HSV-1 infected murine microglial cells, ROS mediated the regulation of some inflammation pertinent signaling, such as p38MAPK and Erk1/2 pathways [ 13 ]. In contrast, the activation of p38MAPK and Erk1/2 signaling by BoHV-1 infection is not mediated by over-produced ROS [ 14 ], though BoHV-1 and HSV-1 are genetically closed [ 9 ]. How BoHV-1 infection contributes to ROS production and the activation of p38MAPK and Erk1/2 signaling has yet to be found.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that c-Jun-dependent trans-activation supports HSV-1 replication in cell cultures ( McLean and Bachenheimer, 1999 ). Similarly, BoHV-1 infection activates the JNK/c-Jun cascade, with inhibition of this pathway via the chemical inhibitor SP600125 significantly blocking productive infection in cell cultures ( Zhu et al, 2016 ). However, how c-Jun signaling is affected by virus infection remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%